Loss of Faith and Decrease in Trust in a Higher Source During COVID-19 in Germany - Büssing, Arndt (Journal of religion and health, 2022)
Many people relied on their faith as one resource in order to cope during the COVID-19 pandemic. In Germany, between the eighteen months from June 2020 to November 2021, different participants at different times were assessed during different phases of the COVID-19 pandemic. The total sample of this continuous cross-sectional survey consisted of 4,693 participants. Analyses revealed that with the 2nd wave of the infection and its 2nd lockdown, trust in a Higher Source, along with praying and meditation decreased. Also, the sharp increase in corona-related stressors was associated with a decline of wellbeing and a continuing loss of faith. These developments were observed in both Catholics and Protestants, and in both younger and older persons. In addition, the long phases of insecurity and social isolation lacking the significant support usually given by religious communities may have likewise challenged the religious-coping capacities of religious/spiritual people themselves.